AKT1E17K‐mutated meningioma cell lines respond to treatment with the AKT inhibitor AZD5363. (30th December 2021) - John, Peter; Waldt, Natalie; Liebich, Josephine; Kesseler, Christoph; Schnabel, Stefan; Angenstein, Frank; Sandalcioglu, I. Erol; Scherlach, Cordula; Sahm, Felix; Kirches, Elmar; Mawrin, Christian
Abstract: Aims: Meningiomas are the most frequent primary brain tumours. Recently, knowledge about the molecular drivers underlying aggressive meningiomas has been expanded. A hotspot mutation in the AKT1 gene ( AKT1 E17K ), which is found in meningiomas at the convexity and especially at the skull base, has been associated with earlier tumour recurrence. Methods: Here, we analysed the effects of the AKT1 E17K mutation and treatment response to the Akt inhibitor AZD5363 in transgenic meningioma cell clones and mouse xenografts modelling convexity or skull base meningiomas. Results: We show that the AKT E17K mutation significantly enhances meningioma cell proliferation and colony size in vitro, resulting in significantly shortened survival times of mice carrying convexity or skull base AKT1 E17K xenografts. Treatment of mutant cells or xenografts (150 mg/kg/d) with AZD5363 revealed a significant decrease in cell proliferation and colony size and a prolongation of mouse survival. Western blots revealed activation of AKT1 kinase (phosphorylation at Ser273 and Thr308) by the E17K mutation in human meningioma samples and in our in vitro and in vivo models. Conclusions: Our data suggest that AKT1 E17K mutated meningiomas are a promising selective target for AZD5363. Abstract : Orthotopic IOMM‐Lee meningioma xenografts overexpressing AKT1 E17K are more aggressive than xenografts with AKT1 wt and can be treated successfully with the AKT inhibitor AZD5363.